Teaching Astronomy in Kindergarten: Children's Perceptions and Projects - Ayala Raviv; Miri Dadon (Athens Institute for Education and Research, 2021)
Young children are familiar with astronomical phenomena from everyday life, such as the movement of the celestial bodies or the shift from day to night. The present study examines the extent to which kindergarten students understand abstract concepts related to celestial bodies and processes (such as gravity and time), and whether they change their perceptions of these concepts following an educational intervention. The study also examines what children report about this learning experience. The study, conducted in a kindergarten in Israel with 32 students, combined quantitative and qualitative research methods. The children's knowledge of astronomy was examined before and after the intervention. The teacher conducted observations, collected the children's creative projects, and interviewed them. She also asked them if they enjoyed the learning process and why. The findings show that few of the children had knowledge about concepts related to astronomy prior to the learning process, and some expressed misconceptions. Following the intervention, there was a significant increase in the children's knowledge and ability to explain astronomical concepts and many of their previously expressed misconceptions had been corrected. Most of the children said they were interested in learning, although some said they felt fear during the lessons. The results indicate that kindergarten students are able to study topics related to astronomy, although they are abstract and difficult to demonstrate. The conclusion of the study is that teachers should be encouraged to integrate studies of astronomy and space into the science curricula for kindergartens. This should be done using appropriate pedagogy that will increase the children's interest and involvement in learning and avoid causing them fears.